2022
DOI: 10.1039/d1ra09124g
|View full text |Cite
|
Sign up to set email alerts
|

Improving the EMI shielding of graphene oxide (GNO)-coated glass-fiber–GNO–MA-grafted polypropylene (PP) composites and nylon 1D–2D nanocomposite foams

Abstract: The proliferation of the latest electronic gadgets and wireless communication devices can trigger electromagnetic interference (EMI), which has a detrimental impact on electronic devices and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Results have confirmed that the EMI shielding properties were strongly associated with the shielding materials' ECs and magnetic permeabilities 62–64 . Many materials with outstanding electrical or magnetic conductivities have been applied in EMI shielding fields 65,66 . EMI shielding materials mainly include metal, inorganic, polymer composites, and so forth 67,68 .…”
Section: Research Progress Of Emi Shielding Materialsmentioning
confidence: 64%
See 1 more Smart Citation
“…Results have confirmed that the EMI shielding properties were strongly associated with the shielding materials' ECs and magnetic permeabilities 62–64 . Many materials with outstanding electrical or magnetic conductivities have been applied in EMI shielding fields 65,66 . EMI shielding materials mainly include metal, inorganic, polymer composites, and so forth 67,68 .…”
Section: Research Progress Of Emi Shielding Materialsmentioning
confidence: 64%
“…[62][63][64] Many materials with outstanding electrical or magnetic conductivities have been applied in EMI shielding fields. 65,66 EMI shielding materials mainly include metal, inorganic, polymer composites, and so forth. 67,68 It should be pointed out that the CPCs filled with hybrid carbonbased/metallic/magnetic fillers have become the most promising materials for EMI shielding.…”
Section: Research Progress Of Emi Shielding Materialsmentioning
confidence: 99%
“…These results indicate that the PDMS-NH 2 were successfully grafted on GO and then chemically reduced to PDMS-NH 2 -g-G, which are consistent with FTIR and Raman results. In the C1s spectrum of PI-MAg-G, the peak of C OH disappeared, and the concentration of C O C and O C O groups is much lower than that of GO, implying that most of the maleic anhydride of PI-MA reacted with the C OH groups of GO surface, 31,41,42 followed by the chemical reduction of oxygenated groups (Figure 3c).…”
Section: Characterization Of Pdms-nh 2 -G-g and Pi-ma-g-gmentioning
confidence: 99%
“…For this reason, EMI shielding polymer nanocomposites are often prepared using conductive filler materials with excellent dielectric and magnetic properties, such as carbon black, carbon nanotubes (CNTs), graphene, , metal nanoparticles, conductive polymers, and core–shell composites . Many zero- (0D), one- (1D), two- (2D), and three-dimensional (3D) materials have also been studied and combined to create conductive filler materials. Furthermore, it has been shown that the EMI shielding efficiency (SE) of a filler material is also significantly affected by its structural characteristics.…”
Section: Introductionmentioning
confidence: 99%